The Influence of Pedagogical Competence, Work Ethic, and Work Motivation on Effective Learning at SMP IT Al-Kamal and MTs Darul Musthofa in 2023 - Utomo, Agung Panji; Ahyar, Ahyar; Thohri , Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study aims to examine the influence of pedagogical competence, work ethic, and work motivation on effective learning at SMP IT Al-Kamal and MTs Darul Musthofa in 2023. This research uses a quantitative approach with non-probability sampling or total sampling techniques. Prerequisite tests include normality, linearity, and multicollinearity tests. Hypothesis testing is conducted using F and T tests, analyzed with SPSS 16.0 software. The results show that pedagogical competence does not significantly influence effective learning (|t| = 0.074 < t_table = 2.018, p = 0.941 > 0.05). Similarly, work ethic does not have a significant impact (|t| = 0.041 < t_table = 2.018, p = 0.967 > 0.05). However, work motivation significantly affects effective learning (|t| = 21.560 > t_table = 2.018, p < 0.05). Additionally, the combined influence of pedagogical competence, work ethic, and work motivation is significant (F = 158.617 > F_table = 3.214, p < 0.05), contributing 92.1% to effective learning outcomes (R² = 0.921). The conclusion of this study emphasizes that work motivation is an essential factor in optimizing effective learning. Theoretical implications suggest the need for further efforts to enhance the influence of pedagogical competence and work ethic in various student contexts.